Identification and Validation of Autophagy-Related Genes in Necrotizing Enterocolitis - Tian, Yuxin; Mao, Mengjia; Cao, Xuqing; Zhu, Haitao; Shen, Chun (Frontiers in Pediatrics, 2022)
Background: Autophagy plays an essential role in the development of Necrotizing enterocolitis (NEC). We aim to identify and validate the potential autophagy-related genes of NEC through bioinformatics analysis and experiment validation. Methods: The differentially expressed autophagy-related genes of NEC were identified by analyzing the RNA sequencing data of experiment neonatal mouse model and dataset GSE46619. Then, protein-protein interactions (PPI), gene-ontology (GO) enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis were applied for the differentially expressed autophagy-related genes. Finally, co-expressed autophagy-related genes in two datasets were identified by Venn analysis and verified by qRT-PCR in experimental NEC. Results: Autophagy increased in experimental NEC and 47 differentially expressed autophagy-related genes were identified in experimental NEC by RNA-sequencing. The PPI results demonstrated that these autophagy-related genes interacted with each other. The GO and KEGG enrichment analysis of differentially expressed autophagy-related genes indicated several enriched terms related to autophagy and macroautophagy. Furthermore, 22 differentially expressed autophagy-related genes were identified in human NEC from dataset GSE46619. The GO and KEGG enrichment analysis of these genes showed similar enriched terms with the results in experimental NEC. Finally, HIF1a, VEGFA, ITGA3, ITGA6, ITGB4 and NAMPT were identified as co-expressed autophagy-related genes by Venn analysis in human NEC from dataset GSE46619 and experimental NEC. The result of qRT-PCR showed the expression levels of HIF-1a and ITGA3 upregulated, VEGFA and ITGB4 downregulated in experimental NEC. Conclusion: We identified 47 differentially expressed autophagy-related genes in experimental NEC and 22 autophagy-related genes in human NEC through bioinformatics analysis. HIF-1a, ITGA3, VEGFA and ITGB4 may affect the development of NEC by regulating autophagy.